1996
DOI: 10.3406/paleo.1996.4625
|View full text |Cite
|
Sign up to set email alerts
|

The Middle Pleistocene Lithic Assemblage from Yarimburgaz Cave, Turkey.

Abstract: Excavations in the lower chamber of Yanmburgaz cave, located a short distance west of the city of Istanbul, have yielded a large assemblage of stone artifacts and a fauna dominated by Ursus deningeri. The strata yielding these materials are of probable Middle Pleistocene age. The lithic assemblage consists primarily of steeply retouched and often extensively modified flake tools, along with smaller numbers of unifacial choppers. Neither bifaces nor Levallois technology are represented. A striking aspect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 1 publication
0
16
0
1
Order By: Relevance
“…Paleolithic artifacts are found in the uppermost seven layers. 36,37 The dating of the Lower Paleolithic deposits at Yarım-burgaz is problematic. Electron spin resonance dates on cave-bear teeth range from Oxygen Isotope Stage 6 through Stage 9.…”
Section: Lower Paleolithicmentioning
confidence: 99%
See 1 more Smart Citation
“…Paleolithic artifacts are found in the uppermost seven layers. 36,37 The dating of the Lower Paleolithic deposits at Yarım-burgaz is problematic. Electron spin resonance dates on cave-bear teeth range from Oxygen Isotope Stage 6 through Stage 9.…”
Section: Lower Paleolithicmentioning
confidence: 99%
“…It is suspected that the consistency and the clast shape of different raw materials were important influences on divergent reduction techniques at Yarımburgaz Cave. 35,37 The Yarımburgaz archeofauna is dominated by an extinct bear (Ursus deningeri), which accounts for nearly 95% of the large vertebrate remains: At least 42 individuals are represented. The bear remains show no evidence of human intervention, although damage resulting from scavenging by large adult bears and other carnivores can be observed.…”
Section: Lower Paleolithicmentioning
confidence: 99%
“…It is evident that the experimental and archaeological sample needs to be expanded to ensure valid quantitative and statistical studies and reinforce our hypotheses. Nevertheless, based on our results we believe that at Azokh Cave, bears (Ursus spelaeus) affected the PDSM of lithic and faunal assemblages (Asryan et al in press and Marin-Monfort et al in press) as is indicated at many other bear den sites (Baryshnikov & Hoffecker 1994;Kuhn et al 1996;Stiner et al 1996;Golovanova et al 1999;Stiner 1999;Quiles et al 2004;Moncel & Rivals 2011). The results of our bear trampling experiment clearly demonstrate that in a short period of time, bears can cause horizontal and some vertical dispersion of artefacts as well as some macro-and microscopic alterations on them.…”
Section: Discussionmentioning
confidence: 89%
“…Kuhn et al (1996) and Schick (1998) Peninsula (Bae 1987;Norton et al, 2006). Of these, Yunxian is Early Pleistocene, Bose likely ca.…”
Section: ) Methodological Issuesmentioning
confidence: 99%